Analisis Kemandrian Keuangan Daerah Di Era Otonomi Pada Pemerintah Kabupaten Tabanan - Mahardika, I Gusti Ngurah Suryaadi; Sri Artini, Luh Gede (E-Jurnal Manajemen, 2014)
The aim of this research is to know the rate of autonomous, effectiveness, and efficiency of financial performance from Tabanan regency’s government. This research was did for period 2007 until 2011. the type of this research is descriptive research. based from analysis, we found that the rate of autonomous financial performance from Tabanan regency’s government during fiscal year 2007 until 2011 is 16,33%, rate of local financial capability is 101,62%, the effectiveness of government revenue is 120,29%, and average efficiency rate is 14,77%. Keywords : autonomous, ability, effectiveness, efficiency Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:IN;}